The Effect of Health Promotion on Adolescents’ Knowledge Regarding Breast Self-Examination (BSE) at Trisakti Junior High School Lubuk Pakam in 2025 - Nurianti, Irma; Batubara, Jernih Dekosta (JURNAL KESMAS DAN GIZI (JKG), 2025)
Breast cancer remains one of the leading causes of mortality among women globally. Early detection through Breast Self-Examination (BSE) is an essential preventive measure to reduce the risk of late diagnosis. Nevertheless, the level of knowledge among adolescents regarding BSE is still relatively low, indicating the need for effective health promotion interventions to enhance understanding and foster positive attitudes toward early detection. Educational media-based health promotion is expected to improve adolescents’ awareness and encourage autonomous practices in performing BSE. This study aimed to evaluate the effectiveness of health promotion delivered through leaflet and animated video media in improving adolescents’ knowledge, attitudes, and practices regarding BSE in a junior high school setting. The research applied a pre-experimental design with a one-group pre-test–post-test approach. A total of 41 students from Trisakti Private Junior High School, Lubuk Pakam, participated as respondents. The intervention consisted of health education using leaflet and animated video media. Data were collected through questionnaires measuring knowledge, attitudes, and practices before and after the intervention. The Wilcoxon signed-rank test was employed to analyze the significance of differences between pre- and post-intervention scores. The findings revealed a statistically significant improvement across all measured variables, particularly in adolescents’ knowledge about BSE (p = 0.000). The mean knowledge score increased from 6.07 prior to the intervention to 7.44 afterward. Moreover, significant enhancements were also observed in attitudes and practices following the intervention. These results indicate that health promotion using leaflet and animated video media is effective in increasing adolescents’ knowledge, attitudes, and practices toward performing BSE. Continuous implementation of such educational programs is recommended to foster awareness and proactive health behavior among adolescents in early breast cancer detection.